Exploring the effect of carbon nanoparticle tracing technique on five-year overall survival and disease-free survival in patients undergoing radical surgery for colorectal cancer: a retrospective study - Wen, Guangxu; Jia, Zihao; Wang, Yingying; Kang, Qingjie; Hu, Denghua; Wang, Ziwei (Frontiers in Oncology, 2024)
BackgroundTo investigate the effect of preoperative carbon nanoparticle tracing technique via colonoscopy on the five-year overall survival and disease-free survival rates in patients undergoing radical resection for colorectal cancer.MethodsA retrospective cohort study was conducted to collect data from patients diagnosed with colorectal cancer who underwent radical resection with complete postoperative pathological information at the First Affiliated Hospital of Chongqing Medical University from March 2013 to February 2017. Patients with multiple primary cancers were excluded, resulting in 2,237 eligible patients in the study. Of these, 368 patients were lost to follow-up within five years after surgery, resulting in a final sample of 1,869 patients. These patients were then divided into two groups: 758 patients who underwent preoperative carbon nanoparticle tracing technique via colonoscopy (CAS group) and 1,111 patients who did not undergo carbon nanoparticle tracing (non-CAS group). Survival curves for both overall survival and disease-free survival were plotted for both groups based on follow-up results. Univariate and multivariate analyses were performed to investigate the effect of carbon nanoparticle tracing technique on the 5-year overall survival and disease-free survival rates in patients, as well as to explore the factors influencing these outcomes.ResultsThe results showed that the total number of lymph nodes detected in the tracing group 15(11,19) was significantly higher than that in the non-tracing group 11(7,15), with a statistically significant difference (p<0.05). The 5-year overall survival rates were 90.8% in the CAS group and 87.4% in the non-CAS group, and, while the disease-free survival rate were 88.5% and 83.4%, respectively. However, the differences between 5-year overall survival and disease-free survival between the two groups were not statistically significant (p>0.05). Both univariate and multivariate cox regression analyses demonstrated that patient age, tumor stage, postoperative chemoradiotherapy, postoperative radiotherapy, and postoperative tumor recurrence were independent factors influencing the 5-year overall survival and disease-free survival rates in colorectal cancer patients.ConclusionCarbon nanoparticle tracing technique can effectively increase the total detected number of lymph nodes in patients with radical resection for colorectal cancer, but it does not significantly impact the 5-year overall survival and disease-free survival rates in these patients.